Use and management of wild fauna by people of the Tehuacán-Cuicatlán Valley and surrounding areas, Mexico - Mariana Zarazúa-Carbajal; Michelle Chávez-Gutiérrez; Yessica Romero-Bautista; Selene Rangel-Landa; Ana Isabel Moreno-Calles; Luis Fernando Alvarado Ramos; Sandra E. Smith; José Blancas; Ek del Val; María del Coro Arizmendi; Alejandro Casas (BMC, 2020)
Abstract Background Interactions between humans and fauna lay in the heart of the history of human subsistence. In Mesoamerica, the Tehuacán-Cuicatlán Valley (TCV) harbours a high biodiversity with archaeological and ethnoecological evidence of its use by people inhabiting the area since at least 12,000 B.P. It is recognized as one of the most ancient areas of agriculture in the Americas, and a broad spectrum of management practices aimed to ensure the availability of desirable plants has been documented, but it has not been analysed for animals. This study aimed to investigate the use and management practices directed to wild animals along current settlements within the TCV and neighbouring areas. Methods We conducted an extensive search, review and analysis of documental sources for the period between 1967 and 2018. We found 38 documents providing information about the presence of animal species and 15 describing their use and/or management. We included our own observations from four case studies among the Ixcatec, Cuicatec, Nahua and Mestizo people, as well as from regional studies of biodiversity. We used unconstrained multivariate data analysis to describe the management typology of the animals in the region. Results Hitherto, 652 vertebrate species and 765 species of insects have been recorded in this area; and until present, 107 wild animal species have been reported to be used in 11 use-type categories, mostly for food (65.42%), ornamental (27.52%) and medicinal (21.10%) purposes by the Nahua, Cuicatec, Popolocan, Ixcatec, Mazatec and Mestizo people. Their extraction entails manual capture and gathering as well as hunting and trapping strategies, some of them involving planning in time or space and communitarian regulations; in addition, relocation actions and care in captivity were recorded. Nearly 178 of the species distributed in the region with no reports of local use are used in other localities of Mesoamerica. Ethnozoological information is still lacking for the Mixtec, Chinantec and Chocholtec people in the area. Conclusions Wild fauna is still a valuable resource for the inhabitants of the TCV. Animals are obtained through extractive practices, which vary from one another in their qualitative attributes. With this work, we provide a context for further research priorities on fauna management in a region of high biocultural significance.